Characteristics of Peel Off Gel Mask From Seaweed (Eucheuma cottonii) Porridge - Novi Luthfiyana; Nurhikma Nurhikma; Taufik Hidayat (Jurnal Pengolahan Hasil Perikanan Indonesia, 2019)
The aim of this study was to determine the best concentration of E. cottonii seaweed porridge in the formulation of peel off gel masks. The main materials used in this study were E. cottonii and other basic substances of peel off gel mask. The analytical methods used were the total microbial and antioxidant test on the E. cottonii slurry preparation. Mask preparations were analyzed for physical stability, pH, duration of preparation, drying, viscosity and homogeneity. The experimental design used was a Completely Randomized with four treatments by adding E.cottonii porridge 0%, 10%, 15% and 20% respectively  with two replications.The results showed that the best peel off gel mask was formulation with the addition 20% of E.cottonii. Microbes were not found in E. cottonii porridge. The antioxidant activity of E. cottonii porridge had IC50 value of 137.35±0.35 μg / mL. Consumer acceptance of products through sensory testing in the category of likes. The peel off gel mask has good physical stability, proven by no changes in color, odor as well as  gel texture. The pH value of the preparation of peel off gel mask is  in line with  SNI and pH balance of normal human skin. The best viscosity value of peel off gel mask is 14,003 cps. The time needed for the mask to dry for an average of 25 minutes and homogeneity is characterized by the absence of secondary particle aggregation.